Rancangan Sistem Rekomendasi “WeShare!” Berdasarkan Kelayakan User Interface - Wati, Zulfazazalia Putri Candra; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
"WeShare!" is a web-based app created to solve the growing problem of clothing and food waste. This website provides users with recommendations about food sharing and preloved clothing. Before being implemented for the public, this system was made into a prototype and evaluated for its feasibility, especially in terms of the user interface. One of the methods used for evaluating the feasibility is the System Usability Scale (SUS) method. In this study, the SUS value of this system design reached 70.42553191. From this value, it can be said that the website prototype is in the Good or "B" grade so that it can be continued and developed to the next stage to be better.